Familial confounding of the association between maternal smoking in pregnancy and autism spectrum disorder in offspring. Issue 1 (29th August 2019) - Kalkbrenner, Amy E.; Meier, Sandra M.; Madley‐Dowd, Paul; Ladd‐Acosta, Christine; Fallin, Margaret Daniele; Parner, Erik; Schendel, Diana
Abstract : Evidence supports no link between maternal smoking in pregnancy and autism spectrum disorder (autism) overall. To address remaining questions about the unexplained heterogeneity between study results and the possibility of risk for specific autism sub‐phenotypes, we conducted a whole‐population cohort study in Denmark. We followed births 1991–2011 (1, 294, 906 persons, including 993, 301 siblings in 728, 271 families), from 1 year of age until an autism diagnosis (13, 547), death, emigration, or December 31, 2012. Autism, with and without attention deficit hyperactivity disorder (ADHD) and with and without intellectual disability (ID) were based on ICD‐8 and ICD‐10 codes from Danish national health registers, including 3, 319 autism + ADHD, 10, 228 autism − no ADHD, 2, 205 autism + ID, and 11, 342 autism − no ID. We estimated hazard ratios (HRs) and 95% confidence intervals (95% CIs) between any maternal smoking (from birth records) and autism (or sub‐phenotypes) using survival models with robust standard errors, stratifying by birth year and adjusting for child sex, parity, and parental age, education, income, and psychiatric history. To additionally address confounding using family designs, we constructed a maternal cluster model (adjusting for the smoking proportion within the family), and a stratified sibling model. Associations with maternal smoking and autism were elevated in conventional adjusted analyses (HR of 1.17 [1.13–1.22]) but attenuated in the maternal cluster (0.98 [0.88–1.09]) and sibling (0.86 [0.64–1.15]) models. Similarly, risks of autism sub‐phenotypes with maternal smoking were attenuated in the family‐based models. Together these results support that smoking in pregnancy is not linked with autism or select autism comorbid sub‐phenotypes after accounting for familial confounding. Autism Res 2020, 13: 134–144 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Smoking during pregnancy has many harmful impacts, which may include harming the baby's developing brain. However, in a study of thousands of families in Denmark, it does not appear that smoking in pregnancy leads to autism or autism in combination with intellectual problems or attention deficits, once you account for the way smoking patterns and developmental disabilities run in families.